A Redefined Approach to Student Assessment Based on Essay Writing in ESP - Božić Lenard, Dragana; Liermann-Zeljak, Yvonne; Ferčec, Ivanka (Collection of Papers of the Faculty of Philosophy in Priština, 2018)
Fierce competitiveness of admission to highly respected universities and companies has created the need to evaluate and profile successful candidates. Traditional evaluation of candidates involving their grades is no longer satisfactory and does not provide a clear image of a candidate. There should be a way to profile a candidate and predict one’s success ranging from a success in a course to a working position. Our research aimed to study potential correlations of students’ writings and their revision exam grades acquired in English for Specific Purposes courses. 203 university engineering students submitted their introductory essays for the computational (LIWC) and statistical (SPSS) analysis. The results showed that the higher achievers used more scholarly vocabulary and verbose sentences. They were task-oriented thinking in a categorical way. On the other hand, the lower achievers used less complex sentences and were other-oriented, demonstrating a verbal dynamic style. However, stereotypical behaviour was only exhibited by the male students, i.e. due to societal pressure, the female students put more effort into their task completion, compensated for the lack of knowledge attempting to establish themselves in the male-dominated field.
Keywords: essays; assessment; correlation; revision exam grades; LIWC; SPSS; ESP